Rural Development: Problems and Suggestive Measures in Assam: Addressing Challenges of Rural Development in Assam (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Rural development is a strategy of development designed to make the rural people develop in respect of the economic and social life. It requires using natural and human resources, techniques, infrastructural facilities, govt. schemes and projects to provide proper education, works and improve the quality of human life in the rural societies. In the process of development, the rural people have to face many problems such as poverty, poor infrastructure, less awareness, poor health etc.